Usability Evaluation of Sistem Informasi Teknik Industri (SITI) Using Performance Measurement - Theresia Venesa Silalahi; Sigit Rahmat Rizalmi; Ahmad Jamil (Universitas Islam Raden Rahmat, Malang, 2025)
Sistem Informasi Teknik Industri (SITI) is a web application developed by the Industrial Engineering Study Program, Kalimantan Institute of Technology, for interaction media between lecturers and students in Kerja Praktek (KP) and Tugas Akhir (TA). In the digital era, information systems play an important role in increasing efficiency and effectiveness in the field of education. This study aims to evaluate the usability of SITI using the Performance Measurement method, namely in the aspects of effectiveness and efficiency. The evaluation results showed that SITI had a very good level of effectiveness, with a task completion rate of 81.25% for lecturers and 81.82% for students. The average error rate reached 21.25% for lecturers and 9.95% for students, especially in the KP and TA guidance filling feature. However, the efficiency still needs to be improved, with a time-based efficiency of 0.09 goals/second for lecturers and 0.038 goals/second for students, as well as an overall relative efficiency of 67.03% for lecturers and 83.1% for students. SITI is effective in supporting academic interaction but needs improvements to features that have a high failure rate to improve efficiency and user experience.